Interview with artist and professor Dr. Rui Serra (Faculty of Fine Arts, Lisbon University, Portugal) (Revista Apotheke, 2024)
Interview conducted with Rui Serra in the first half of 2023, in person at the artist’s private studio, in Lisbon, Portugal, on the occasion of international cooperation between the Apotheke Painting Studio and the Faculty of Fine Arts of the University of Lisbon, via CNPq Notice No. 26/2021, coordinated by Full Professor Dr. Jociele Lampert (UDESC).
Keywords: Rui Serra; painting; Internacional Apotheke